2019
DOI: 10.30630/polingua.v8i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal Analysis on Thailand Advertisement

Abstract: Communication occurs when one can express his/her opinion, thought, idea on people, things and situations. Opinion-related meanings in language are regarded as resources of evaluation or appraisal in language. Not necessarily good or bad in a moral sense, attitude accompanies the language utterance every person utters. As one kind of appraisal resources, attitude plays an important role in the expression of interpersonal meanings of language. Attitude refers to a way that you behave towards someone or in a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…(1) affect, concerning positive and negative feelings; (2) judgement, dealing with behavior; and (3) appreciation, evaluating semiotic and natural phenomena. Those explorations concern on attitude by involving explicit and/or implicit ways to decide affect, judgment, or appreciation (Martin & Rose 2003;Martin & White 2004;Wijaya et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…(1) affect, concerning positive and negative feelings; (2) judgement, dealing with behavior; and (3) appreciation, evaluating semiotic and natural phenomena. Those explorations concern on attitude by involving explicit and/or implicit ways to decide affect, judgment, or appreciation (Martin & Rose 2003;Martin & White 2004;Wijaya et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Appraisal and attitude analyses are also applicable to the discourse used in commercial uses such as product advertisement (Wijaya et al 2019) and promoting tourist destination (Suryaningtyas et al 2019). Nazhira et al (2016), Nurjanah (2021); Suryaningtyas et al (2019), Wijaya et al (2019) have shown good progress of attitude and appraisal in SFL studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies predominantly focused on investigating the use of attitude resources in students' argumentative texts (e.g., Fauziah et al, 2019;Jalilifar & Hemmati, 2013;Ngongo, 2017;Solihah, 2020;Yang, 2016;Xinghua & Thompson, 2009) and in narrative texts (e.g., Fitriati et al, 2018). Studies concerning the use of attitude resources are widely conducted to examine how professional bloggers make use of these resources (e.g., Mocini, 2013;Ho & Suen, 2017;Wijaya et al, 2019;Wu, 2013). There is a study examining how students use attitude resources in a promotional text conducted by Marsakawati et al (2019) however, the focus was on spoken business presentation.…”
Section: Introductionmentioning
confidence: 99%